Acute effects of intravenous carvedilol versus metoprolol on baroreflex-mediated sympathetic circulatory regulation in rats. (15th June 2019) - Yamamoto, Hiromi; Kawada, Toru; Shimizu, Shuji; Hayama, Yohsuke; Shishido, Toshiaki; Iwanaga, Yoshitaka; Fukuda, Kanji; Miyazaki, Shunichi; Sugimachi, Masaru
Abstract: Aims: To compare the effects of metoprolol and carvedilol on baroreflex-mediated sympathetic circulatory regulation. Methods: In anesthetized Wistar–Kyoto rats, carotid sinus baroreceptor regions were isolated. Changes in sympathetic nerve activity (SNA), arterial pressure (AP), heart rate (HR), and aortic flow (AoF) in response to a staircase-wise pressure input were examined before (control) and after intravenous injection of low-dose metoprolol (2 mg/kg), high-dose metoprolol (10 mg/kg), or carvedilol (0.67 mg/kg) ( n  = 6 each). Peripheral vascular resistance (PVR) was calculated from mean AP divided by mean AoF. Results: Low-dose metoprolol had limited effect on sympathetic AP regulation compared to control [operating-point AP (drug vs. control): 88.7 ± 7.1 vs. 98.3 ± 3.3 mm Hg, not significant] despite a significant bradycardic effect. Although high-dose metoprolol showed central sympathoinhibition, it increased PVR at a given SNA as a peripheral effect. Consequently, high-dose metoprolol decreased the operating-point AP slightly (96.1 ± 2.7 vs. 101.9 ± 2.7 mm Hg, P  < 0.01). Carvedilol showed no significant central sympathoinhibition at the dose examined in this study, but significantly reduced PVR at a given SNA, leading to a marked reduction in the operating-point AP (71.9 ± 8.2 vs. 112.6 ± 7.6 mm Hg, P  < 0.05). Conclusion: Low-dose metoprolol has limited hypotensive effect despite blockade of sympathetic HR regulation. Although high-dose metoprolol induces central sympathoinhibition, it also induces peripheral vasoconstriction that antagonizes the hypotensive effect. In contrast, carvedilol exhibits hypotensive effect mainly through peripheral vasodilation. Although carvedilol is frequently classified as a β-blocker, its vasodilatory effect via α1 -adrenergic blockade plays an important role in AP reduction or heart failure treatment. Highlights: Metoprolol (ML) and carvedilol (CL) blunted the sympathetic heart rate response. High-dose ML caused a slight central sympathoinhibition. High-dose ML induced peripheral vasoconstriction at a given sympathetic tone. CL did not reduce sympathetic tone but induced peripheral vasodilation. Vasodilation is a feature of CL, it may be beneficial in treating heart failure.